Helvetica [videorecording (DVD)] - Hustwit, Gary (Swiss Dots Limited ; Distributed by Plexifilm, 2007)
A documentary about a typeface? When said typeface is a ubiquitous piece of graphic design, yes. Helvetica--a sans-serif typeface developed in 1957 at the Haas Foundry in Munchenstein, Switzerland--has partisans and detractors, a great number of them graphic designers and theorists, who express their opinions on the famous font. It is seen as neutral and efficient, concise yet inexpressive, purposeful yet not caustic, utilitarian and unembellished, or as frustratingly familiar, perfectly subliminal, or as the typeface of socialism. From storefronts, street signs, product packaging, government forms, and advertisements, it is almost guaranteed that after viewing, you will be scanning the world examining Helvetica's continuing impact.